2022
DOI: 10.1111/1468-5973.12442
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of strategic decision‐making by crisis management teams during exercising: Establishing key dimensions

Abstract: To survive and thrive in a crisis requires crisis management teams (CMTs) to make sound strategic decisions. This paper examines the perceptions of CMTs from a group of nonresponse organisations to identify dimensions of the strategic decision‐making process during a crisis management exercise. The paper draws on data collected during a series of exercises with seven Australian government agencies and businesses. Using principal component analysis, this paper outlines four dimensions that are perceived to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Stakeholder engagement is a valuable intangible resource that permits project management, and it provides a conduit between entrepreneurial orientation and the performance of agricultural projects. These findings are supported by the work of previous scholars (Githinji et al, 2020;Bourne & Walker, 2005;Curnin, Brooks, Owen, & Brooks, 2022), who reveal that engaging stakeholders in project activities is an assured test of project performance. The findings indicate that stakeholders must be absorbed in agricultural project activities, dedicated to work, and enthusiastic about work in order to improve agricultural project performance.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Stakeholder engagement is a valuable intangible resource that permits project management, and it provides a conduit between entrepreneurial orientation and the performance of agricultural projects. These findings are supported by the work of previous scholars (Githinji et al, 2020;Bourne & Walker, 2005;Curnin, Brooks, Owen, & Brooks, 2022), who reveal that engaging stakeholders in project activities is an assured test of project performance. The findings indicate that stakeholders must be absorbed in agricultural project activities, dedicated to work, and enthusiastic about work in order to improve agricultural project performance.…”
Section: Discussionsupporting
confidence: 83%
“…Stakeholder engagement is the process used by an organization to engage relevant stakeholders to manage different risks with a clear purpose to achieve accepted outcomes (Neil, 2009). It is now also recognized as a fundamental accountability mechanism, since it obliges an organization to involve stakeholders in identifying, understanding, and responding to sustainability issues and concerns, and to report, explain, and be answerable to stakeholders for decisions, actions, and performance (Curnin, Brooks, Owen, & Brooks, 2022). Today, prominent projects have started to develop an appreciation that stakeholder engagement can contribute to learning and innovation in products and processes, which further leads to improved productivity.…”
Section: Hypotheses Development Stakeholder Engagement and Project Pe...mentioning
confidence: 99%
“…Indeed, crisis simulation, by its ability to ‘create opportunities for people to work together and to improve their practice of anticipated situations’ (Wybo, 2008, p. 492) enables crisis cells to set up a) the appropriate stressful situations in which to involve a crisis cell composed of different people with different levels and types of expertise and b) the conditions for observation necessary for a scientific analysis. Research has showed that crisis simulation can be used as a reliable tool to analyse crisis management and more specifically the decision‐making process within a crisis cell (Curnin et al, 2022; De Vittoris et al, 2023). Crisis simulations have already been used to demonstrate the role of expertise (Harrald & Mazzuchi, 1993), but have focused on the beneficial effects of the expert's presence within the crisis cell.…”
Section: Methodsmentioning
confidence: 99%
“…As Curnin et al (2022, p.2) point out, ‘the impact of poor decisions has been articulated in a long list of disasters—industrial, natural hazard‐related, and in finance, so there is significant relevance in poor decision‐making’. Numerous studies have investigated the organizational behaviours of multinationals regarding preparedness for crises (Fainshmidt et al, 2017), with particular focus on the decision‐makers and their decision‐making processes (Kuklan, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…From the published studies, however, some indications can be derived regarding the (1) content orientation and (2) methods of evaluations, which have also been incorporated into the design of the present evaluation approach:. Regarding (1) content, some topics can be identified, especially in the somewhat broader literature on the topic of crisis management and staff work, which are repeatedly emphasized as relevant and critical to success: leadership or management (performance) in CT, decision-making and communication, interaction in CT, (interorganizational) work and coordination in terms of common goals, clear structures and processes, responsibilities and competencies, and role clarity, to name the ones most addressed (e.g., Adam and Schaller 2021;Berlin and Carlström 2014;Curnin et al 2022;Gißler 2021;Grunnan and Fridheim 2017;Heumüller et al 2014;Högl 2013;Hofinger 2008;Laurila-Pant et al 2023;Moon et al 2023;Rehfeld 2022;Sørensen et al 2020;Son et al 2020;Strohschneider 2011;Thieme and Hofinger 2008;Trauboth 2022).…”
Section: Basic Points Of Orientation In Terms Of Content and Methodol...mentioning
confidence: 99%